2023
DOI: 10.1111/mbe.12375
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Executive Function in Reading Development and Reading Intervention

Abstract: The current review of the role of executive function (EF) in reading provides a brief summary of analyses with a large‐scale longitudinal dataset and a meta‐analysis, along with proposing a framework for designing EF training studies. The 1st study, based on latent growth models with structured residuals, demonstrated a longitudinal reciprocal relation between reading and EF in Grades 2–5, but only for high‐performing students and not for the general population sample or those with reading difficulties. The 2n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 96 publications
0
2
0
Order By: Relevance
“…This is particularly true for domains in which children must learn new symbolic representations that integrate information across modalities (early reading and math) and those that combine information across levels (reading comprehension and math word problems). Indeed, there is a substantial body of literature linking EFs to reading (Peng, 2023; Butterfuss & Kendeou, 2018; Ober, Brooks, Homer, & Rindskopf, 2020) and math (Peng, Namkung, Barnes, & Sun, 2016) performance. Despite these established relationships, there has been considerable debate over the role of EFs in academic skills with both researchers and practitioners noting that EFs are not well‐specified enough.…”
Section: Commentarymentioning
confidence: 99%
“…This is particularly true for domains in which children must learn new symbolic representations that integrate information across modalities (early reading and math) and those that combine information across levels (reading comprehension and math word problems). Indeed, there is a substantial body of literature linking EFs to reading (Peng, 2023; Butterfuss & Kendeou, 2018; Ober, Brooks, Homer, & Rindskopf, 2020) and math (Peng, Namkung, Barnes, & Sun, 2016) performance. Despite these established relationships, there has been considerable debate over the role of EFs in academic skills with both researchers and practitioners noting that EFs are not well‐specified enough.…”
Section: Commentarymentioning
confidence: 99%
“…Word-level (untimed) skills tend to improve most rapidly, and fluency and comprehension skills more gradually (Donnelly et al, 2019). Self-regulation, here encompassing executive function and socioemotional skills, are likewise recognized as important elements for reading success (Peng, 2023). Children also show differential instructional needs based on their strengths and challenges; research with first graders showed that students with lower decoding skill benefited from teacher-managed explicit decoding instruction, while children with higher vocabulary scores benefited from independent child-managed reading and writing activities (Connor et al, 2004).…”
Section: Reading Acquisition Componentsmentioning
confidence: 99%